Karakteristik Penderita Epilepsi Di Beberapa Lokasi Di Wilayah Indonesia Periode Tahun 2013 Sampai Dengan Tahun 2020 - Nugraha, Aulia; Thamrin, Rahmawati; Zulkarnain, Nanang (Bosowa Medical Journal, 2023)
Epilepsy is a chronic cerebral disease that occurs because of the release of excessive electrical charges of the brain so that it can cause loss of consciousness, involuntary movements, abnormal sensory phenomena, an increase in autonomic activity and various physical disorders. Epilepsy can affect anyone based on different age, gender, occupation, educational history, and family history. In epilepsy there is no single cause. Many factors can injure nerve cells including a history of head trauma, a history of febrile seizures. The consequences for people with epilepsy are shame, anxiety, depression, and lack of self-confidence so that the sufferer will withdraw from the environment and affect the quality of life of the sufferer. This study aims to determine the incidence of epilepsy in several regions in Indonesia based on the  (1) type of rise, (2) age group, and (3) gender. This study is descriptive cross sectional. Data were obtained from various research articles. The study sample was 790 patients. This study took secondary data from various journals. The result of this study is that the type of epileptic awakening occurs more with the rise of generalisata (46%), with the age group occurring more in the productive age group (58%), and more occurring in people of the female sex (51%).